2018
DOI: 10.1063/1.5023857
|View full text |Cite
|
Sign up to set email alerts
|

A recurrence quantification analysis-based channel-frequency convolutional neural network for emotion recognition from EEG

Abstract: Constructing a reliable and stable emotion recognition system is a critical but challenging issue for realizing an intelligent human-machine interaction. In this study, we contribute a novel channel-frequency convolutional neural network (CFCNN), combined with recurrence quantification analysis (RQA), for the robust recognition of electroencephalogram (EEG) signals collected from different emotion states. We employ movie clips as the stimuli to induce happiness, sadness, and fear emotions and simultaneously me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 51 publications
0
28
1
Order By: Relevance
“…In some studies it is reported that SOBI is capable of functionally separating sources which are physiologically interpretable [24][25][26][27]. SOBI is really robust in low SNRs [27][28][29][30][31][32].…”
Section: Blind Source Separation and Sobimentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies it is reported that SOBI is capable of functionally separating sources which are physiologically interpretable [24][25][26][27]. SOBI is really robust in low SNRs [27][28][29][30][31][32].…”
Section: Blind Source Separation and Sobimentioning
confidence: 99%
“…These characteristics motivated us to use SOBI in this study. For further information about SOBI algorithm and its utility refer to [29][30][31].…”
Section: Blind Source Separation and Sobimentioning
confidence: 99%
“…In 2013, Duan proposed a feature extraction method based on differential entropy, which achieved good results on emotion-based datasets [18]. In the past two years, many researchers have used differential entropy as a feature extraction method to achieve good results on different datasets [19,20]. However, researchers often use multi-channel acquisition equipment when collecting EEG data.…”
Section: Introductionmentioning
confidence: 99%
“…Although those existing machine learning algorithms have found successful applications in the field of emotion recognition, some limitations exist. The limitations include deficient learning inheriting characteristics of training samples [44], and its poor classification accuracy due to the subject dependency of emotion [45]. In addition, the existing machine learning algorithms usually also suffer from severe overfitting [46].…”
Section: Introductionmentioning
confidence: 99%
“…Song et al [16] proposed a Graph CNN (GCNN) to dynamically learn the features and discriminate the relationship between different EEG channels, to improve the EEG emotion recognition. Yang et al [44] integrated a nonlinear method—recurrence quantification analysis (RQA)—into a novel channel-frequency convolutional neural network (CFCNN) for the EEG-based emotion recognition, acquired an accuracy of 92.24%, and also proved strong relationship between emotional process and gamma frequency band. A hierarchical CNN (HCNN) method was adopted by Li et al [46] to distinguish the positive, negative and neutral emotion states, the comparable results with stacked auto-encoder (SAE), SVM and KNN shows HCNN yields the highest accuracy.…”
Section: Introductionmentioning
confidence: 99%